Comparison of the Histopathological Findings of Testis Tissues of Non-Obstructive Azoospermia with the Findings after Microscopic Testicular Sperm Extraction - Toksöz, Serdar; Kizilkan, Yalçin (Urology Journal, 2019)
Purpose: To investigate the relationship between the histopathological findings of testis tissue samples and sperm retrieval success of micro-TESE in non-obstructive azoospermia (NOA) patients. Method: Histopathological examination results of the testis tissue samples of 795 NOA patients who underwent micro-TESE operation in our clinic between 2003 and 2014 were included. Histopathological findings were grouped as hypospermatogenesis, incomplete spermatocytic arrest, complete spermatocytic arrest, Sertoli cell only syndrome (SCOS), and fibrosis/atrophy. Chi-square analysis was used to compare the histopathological findings with the sperm retrieval rates of micro-TESE. Result: Sperm was found in 341 (42,9%) patients following micro-TESE compared to 454(57,1%) patients where sperm were not detected (P < 0.001). Sperm retrieval rates of micro TESE were significantly higher in hypospermatogenesis and incomplete maturation arrest groups (93.2% (P < 0.001) and 72.5% (P < 0.001), respectively). Complete maturation arrest, SCOS and fibrosis/atrophy were determined at significantly higher rates in patients (220.2%) with no sperm found compared to patients with sperm (P < 0.001). Conclusion: The findings of this study are consistent with those of previous studies in the literature. Testicular histopathological findings can provide additional data when informing NOA patients about the expected success of further micro-TESE operations.